Biology of cyclooxygenase-2: An application in depression therapeutics - He, Ying; Han, Yuanshan; Liao, Xiaolin; Zou, Manshu; Wang, Yuhong (Frontiers in Psychiatry, 2022)
Depressive Disorder is a common mood disorder or affective disorder that is dominated by depressed mood. It is characterized by a high incidence and recurrence.The onset of depression is related to genetic, biological and psychosocial factors.However, the pathogenesis is still unclear.In recent years, there has been an increasing amount of research on the inflammatory hypothesis of depression, in which cyclo-oxygen-ase 2 (COX-2), a pro-inflammatory cytokine, is closely associated with depression. A variety of chemical drugs and natural products have been found to exert therapeutic effects by modulating COX-2 levels. This paper summarizes the relationship between COX-2 and depression in terms of neuroinflammation, intestinal flora, neurotransmitters, HPA axis, mitochondrial dysfunction and hippocampal neuronal damage, which can provide a reference for further preventive control, clinical treatment and scientific research on depression.